1981
DOI: 10.1002/bjs.1800681206
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in relation to symptom duration in colon cancer

Abstract: Between 1950 and 1978 754 patients underwent operation by one of the authors for carcinoma of the colon. Follow-up data were available on 99 per cent. Tumour stage distribution did not differ significantly with increasing duration of symptoms. The proportion of curative to palliative operative procedures was unrelated to symptom duration. Cancer specific survival for the entire patient series was worse when symptoms had been present for less than 3 months compared with 3-6 months, 6-12 months or 12 months or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 13 publications
1
27
0
5
Order By: Relevance
“…1981 verfolgten McDermott und Hughes die Über-lebenszeit von 754 Kolonkarzinomen. Danach differierten die Dukes-Gruppen A, B und C bei einer Symptomdauer von weniger als 3 Monaten nicht von der mit mehr als 12 Monaten bei gleich bleibender unterschiedlicher Prognose [9]. Wie man leicht sehen kann, verteilen sich die Zahl der Einzelfälle in den Dukes-Gruppen A, B und C auch nach der oben genannten Galton-Regel (.…”
Section: Kommentar Zu Den Beiträgenunclassified
“…1981 verfolgten McDermott und Hughes die Über-lebenszeit von 754 Kolonkarzinomen. Danach differierten die Dukes-Gruppen A, B und C bei einer Symptomdauer von weniger als 3 Monaten nicht von der mit mehr als 12 Monaten bei gleich bleibender unterschiedlicher Prognose [9]. Wie man leicht sehen kann, verteilen sich die Zahl der Einzelfälle in den Dukes-Gruppen A, B und C auch nach der oben genannten Galton-Regel (.…”
Section: Kommentar Zu Den Beiträgenunclassified
“…Results so far have been varied and contradictory. Thus, some authors conclude that there is correlation between a greater delay and a more advanced tumor stage (10)(11)(12), while according to others, this relationship only holds for tumors of the rectum (13)(14)(15) and some have been unable to find any relationship at all (9,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…McDermott et al [4] found a significantly greater proportion of poorly differentiated tumors in patients with symptoms for less than 3 months compared with those presenting with symptoms of 3 and 6 months duration, but not with patients with symptoms of longer duration. Furthermore, they found a worse survival rate in patients with symptoms arising within 3 months compared with those with symptoms of longer duration.…”
Section: Discussionmentioning
confidence: 96%